2015
DOI: 10.1007/164_2015_39
|View full text |Cite
|
Sign up to set email alerts
|

3′,5′-cIMP as Potential Second Messenger in the Vascular Wall

Abstract: Traditionally, only the 3',5'-cyclic monophosphates of adenosine and guanosine (produced by adenylyl cyclase and guanylyl cyclase, respectively) are regarded as true "second messengers" in the vascular wall, despite the presence of other cyclic nucleotides in different tissues. Among these noncanonical cyclic nucleotides, inosine 3',5'-cyclic monophosphate (cIMP) is synthesized by soluble guanylyl cyclase in porcine coronary arteries in response to hypoxia, when the enzyme is activated by endothelium-derived n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Among the cyclic nucleotides, cIMP has been shown to exert vasocontraction (Chen et al, 2014 ; Detremmerie et al, 2016 ). cIMP is the first, in terms of levels detected, of the minor products of sCG (Beste et al, 2012 ; Chen et al, 2014 ) and its biosynthesis requires the endothelium‐derived NO activation of sGC (Leung et al, 2017 ). The homogenised aorta samples from either WT or CSE −/− mice were processed to detected simultaneously cIMP, cGMP and cAMP levels by using UPLC‐MS/MS analysis (Figure 8a,b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the cyclic nucleotides, cIMP has been shown to exert vasocontraction (Chen et al, 2014 ; Detremmerie et al, 2016 ). cIMP is the first, in terms of levels detected, of the minor products of sCG (Beste et al, 2012 ; Chen et al, 2014 ) and its biosynthesis requires the endothelium‐derived NO activation of sGC (Leung et al, 2017 ). The homogenised aorta samples from either WT or CSE −/− mice were processed to detected simultaneously cIMP, cGMP and cAMP levels by using UPLC‐MS/MS analysis (Figure 8a,b ).…”
Section: Resultsmentioning
confidence: 99%
“…3.4 | cAMP, cGMP and cIMP levels are altered in CSE À /À mice aorta Among the cyclic nucleotides, cIMP has been shown to exert vasocontraction (Chen et al, 2014;Detremmerie et al, 2016). cIMP is the first, in terms of levels detected, of the minor products of sCG (Beste et al, 2012;Chen et al, 2014) and its biosynthesis requires the endothelium-derived NO activation of sGC (Leung et al, 2017).…”
Section: Cse à/à Mice Aorta and Carotid Arteries Display Impaired Vasoconstrictionmentioning
confidence: 99%
“…Administration of inosine triphosphate (ITP), the precursor of cIMP, potentiated the hypoxic augmentation, an effect also prevented by sGC-inhibition with ODQ [16]. Hence the conclusion that the "biased" activity of sGC leading to the production of the non-canonical cyclic nucleotide cIMP underlies the increases in isometric tension caused by acute hypoxia in isolated blood vessels [34][35][36]. The switch from the production, by sGC, of cGMP to that of cIMP also explains why relaxations to endothelium-and NO-dependent vasodilators are abolished by hypoxia (pO 2 ≤ 1 mmHg) [5].…”
Section: Obligatory Role Of Soluble Guanylyl Cyclasementioning
confidence: 99%
“…19 Except for cGMP, the maximal rate formation of cIMP is substantially greater than that of other nucleosides. 19,20 In a previous study, we found that the activation of the NO-sGC axis led to increased levels of cIMP (proposed as a novel second messenger 21 ), that further activated Rho kinase, inhibited myosin light chain phosphatase activation and induced constriction in porcine coronary artery. 9 Studies using purified recombinant human phosphodiesterases (PDEs) and 3′,5′-cyclic nucleotide salts showed that cIMP is hydrolysed by a number of types of PDEs as in the case of cGMP.…”
Section: Introductionmentioning
confidence: 97%